The Nipple as a Landmark for Needle Decompression of Tension Pneumothorax in Children – A CT-Based Evaluation and Proposal of an Alternative Insertion Site. (2nd November 2021) - Terboven, Tom; Heblich, Lea A.; Weiss, Christel; Viergutz, Tim; Rudolph, Marcus; Waldeck, Stephan; Schönberg, Stefan; Overhoff, Daniel
Abstract: Objective: Needle decompression of tension pneumothorax in children is a rarely encountered but potentially life-saving procedure, that is accompanied by a certain risk of injury. We evaluated the nipple as a landmark for an alternative anterior insertion site and as an aid in localizing lateral insertion sites, as well as its influence on the safety profile of the procedure. Methods: In thoracic computer tomography scans of children aged 0–10 years, the distance to the closest vital structure was compared between the traditional anterior insertion site (2nd intercostal space midclavicular line) and an alternative anterior insertion site (2nd intercostal space at the nipple line). Furthermore, the level of the nipple at the midaxillary line was investigated as guidance in quickly localizing the lateral insertion site and ensuring an insertion site high enough to avoid intraabdominal injury by the decompression needle. Additionally, correlation of these measures with age was investigated. Results: The distance to the closest vital structure at the 2nd intercostal space was significantly bigger at the nipple line compared to the midclavicular line (right: 2.23 ± 1.13 cm vs. 0.99 ± 0.80 cm, p < 0.0001; left: 1.92 ± 1.19 cm vs. 0.81 ± 0.70 cm, p < 0.0001). At the midaxillary line, the level of the nipple was at the 4th or 5th intercostal space in the majority of children (right: 83.8%; left: 88.1%). The mean distance from the nipple to the diaphragmatic cupola was 2.63 ± 1.85 cm on the right and 3.40 ± 1.86 cm on the left hemithorax. Conclusion: When performing anterior needle decompression in children, we recommend inserting the needle at the more lateral insertion site at the 2nd intercostal space at the nipple line. At the lateral decompression sites, the nipple can be used as a marker for localizing the correct intercostal space for insertion and thereby ensuring enough caudad distance to the diaphragm to avoid abdominal injury.